Punjabi at heart: Language, legitimacy, and authenticity on social media. (June 2015) - Karrebæk, Martha Sif; Stæhr, Andreas; Varis, Piia
Abstract: In this paper we contribute to discussions on the relation between language, place and legitimacy in contemporary globalization, including considerations of mobility, social media, and authenticity. Our empirical case is the Danish born performing artist Anita Lerche. Lerche sings in Punjabi, and in addition to language she deploys other semiotic elements which index India and Punjab. This triggers both negative and positive evaluations from her audience. In some cases, it even triggers (self) criticism of the deficient Punjabiness of Diaspora Punjabis. The overwhelming majority of the responses are based on an ideology of an inherent and natural relation between language and ethnic or geographical belonging. Lerche clearly does not conform to that as she explores her possibilities of identification and professional success beyond traditional borders and territories. The data analyzed consist of discussions on social media, and mainly responses to one of Lerche׳s Facebook posts. Despite the non-local character of the medium, and the different places of residence of the audience, a particular geographical location (Punjab) remains central in the construction of belonging, legitimacy, obligation and authenticity. In addition to data on Lerche׳s Facebook profile, we also draw on interviews with Lerche and some fieldwork.